New lithistid sponge of the genus Sollasipelta (Porifera, Demospongiae,Tetractinellida, Neopeltidae) from submarine caves of the Ryukyu Islands,southwestern Japan, with redescription of S. sollasi - Ise, Yuji; Vacelet, Jean; Mizuyama, Masaru; Fujita, Yoshihisa (Zootaxa, 2023)
A new species of ‘lithistid’ (rock sponge) Sollasipelta subterranea sp. nov. is described from near-shore submarine caves of Okinawa and Shimoji Islands, the Ryukyu Islands, southwestern Japan. This new species is characterized by the smooth dentate ectosomal pseudophyllotriaenes, slender choanosomal oxea/style/subtylostyles and two types of amphiasters, one of which is in two size classes. Sollasipelta subterranea sp. nov. is morphologically closest to Sollasipelta sollasi (Lévi & Lévi, 1989), known from the Philippines deep sea, and our examination of the type specimen of S. sollasi revealed that the pseudophyllotriaenes and desmas are substantially different between the two species, and both species possess two types of amphiasters, one of which has two size classes. Sollasipelta cavernicola (Vacelet & Vasseur, 1965) and S. punctata (Lévi & Lévi, 1983) are transferred to the genus Daedalopelta Sollas, 1888, based on possession of one type of amphiastes as microscleres. Sollasipelta mixta (Vacelet, Vasseur and Lévi, 1976) is formally transferred to the genus Neopelta Schmidt, 1880, based on the morphological characters. A key to species of the genus Sollasipelta Van Soest & Hooper, 2020 is also provided. Sollasipelta subterranea sp. nov. represents the first ‘lithistid’ sponge from submarine caves of the Western Pacific and the first species of sponge inhabiting anchialine cave environments in the Indo-West Pacific. This is also a new record of the family Neopeltidae from Japanese waters.